Fibroblasts derived from patients with opsismodysplasia display SHIP2‐specific cell migration and adhesion defects. Issue 12 (21st September 2017) - Ghosh, Somadri; Huber, Céline; Siour, Quentin; Sousa, Sérgio B.; Wright, Michael; Cormier‐Daire, Valérie; Erneux, Christophe
Abstract: The SH2 domain containing inositol phosphatase 2 (SHIP2) dephosphorylates PI(3, 4, 5)P3 to generate PI(3, 4)P2, a lipid involved in the control of cell migration and adhesion. The INPPL1 gene that encodes SHIP2 has been found to be mutated in several cases of opsismodysplasia (OPS), a rare autosomal recessive chondrodysplasia characterized by growth plate defects and delayed bone maturation. Reported mutations often result in premature stop codons or missense mutations in SHIP2 catalytic domain. SHIP2 biochemical properties are known from studies in cancer cells; its role in endochondral ossification is unknown. Here, we report two novel mutations in the INPPL1 gene and show that cell migration is very much decreased in fibroblasts derived from three OPS patients as compared with control individuals. In contrast, cell adhesion on fibronectin is increased in OPS fibroblasts. An inhibitory effect on migration was also observed when normal fibroblasts were incubated in the presence of a SHIP2 competitive inhibitor. We conclude that both migration and adhesion are very much disrupted in OPS‐derived fibroblasts. It is suggested that signaling events linked to migration and particularly to adhesion, which are lost in OPS patients, would prevent normal endochondral ossification. Abstract : The phosphatase SHIP2 dephosphorylates PI(3, 4, 5)P3 to PI(3, 4)P2, a lipid involved in the control of cell migration. The INPPL1 gene that encodes SHIP2 has been found to be mutated in several cases of opsismodysplasia, a rare autosomal recessive chondrodysplasia characterized by growth plate defects and delayed bone maturation. Ghosh et al report two novel mutations in the INPPL1 gene and show that cell migration is very much decreased in fibroblasts derived from three OPS patients as compared to control individuals.